2020
DOI: 10.1038/s41598-020-72271-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of air pollution over 41 cities of India during the COVID-19 lockdown period

Abstract: In this study, we characterize the impacts of COVID-19 on air pollution using NO2 and Aerosol Optical Depth (AOD) from TROPOMI and MODIS satellite datasets for 41 cities in India. Specifically, our results suggested a 13% NO2 reduction during the lockdown (March 25–May 3rd, 2020) compared to the pre-lockdown (January 1st–March 24th, 2020) period. Also, a 19% reduction in NO2 was observed during the 2020-lockdown as compared to the same period during 2019. The top cities where NO2 reduction occurred were New De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(76 citation statements)
references
References 18 publications
2
72
0
2
Order By: Relevance
“…In this paper, the cumulative number of confirmed COVID-19 cases was taken as a variable, the spatial weight matrix based on geographical adjacency was selected, and the global Moran's I index, P test value, and Z statistical score were used to determine the number of confirmed cases with different types of neighbors ( Vadrevu et al, 2020 ).To investigate whether there is a spatial correlation between confirmed COVID-19 cases in China. ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, the cumulative number of confirmed COVID-19 cases was taken as a variable, the spatial weight matrix based on geographical adjacency was selected, and the global Moran's I index, P test value, and Z statistical score were used to determine the number of confirmed cases with different types of neighbors ( Vadrevu et al, 2020 ).To investigate whether there is a spatial correlation between confirmed COVID-19 cases in China. ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a retrospective spatio-temporal scanning statistical method was used to include a time dimension in the analysis and to determine when, where, and when the cluster occurred (and for how long) ( Vadrevu et al, 2020 ). Because COVID-19 is transmitted from person to person, and more cases are likely to occur in densely populated areas, we selected the Poisson model in SaTScan to calculate the population in each area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing literature studying and trying to estimate the impact of the pandemic on air pollution. Evidence of reductions in air pollution following the outbreak of the pandemic was found in many regions, such as Egypt ( Mostafa et al, 2021 ), the USA ( Liu et al, 2021 ), the UK ( Ropkins and Tate, 2021 ), and India ( Singh et al, 2020 ; Vadrevu et al, 2020 ). In the context of China, several recent studies found similar evidence that the variation in air pollution concentration in many regions of China dropped significantly during the pandemic ( Bao and Zhang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies around the world, as in China and East Asia [13][14][15], India [16][17][18], Southeast Asia [19,20], Europe [21][22][23][24][25][26], North America [27,28] and South America [29,30], have analyzed the effect of COVID-19 lockdowns in spring 2020 on concentrations of particulate matter (PM) and gaseous pollutants (NO x , CO, O 3 , SO 2 , NH 3 , etc.). All these studies agree on an unprecedented reduction of air pollution worldwide due to drastic limitations in traffic and industrial activity [31][32][33].…”
Section: Introductionmentioning
confidence: 99%